2015
DOI: 10.1186/s12944-015-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 C3435T polymorphism and the lipid-lowering response in hypercholesterolemic patients on statins: a meta-analysis

Abstract: BackgroundA number of researches have evaluated the association between the ABCB1 polymorphism and the lipid-lowering response of statins, but the results have been inconclusive. To examine the lipid-lowering efficacy and safety associated with the ABCB1 C3435T polymorphism in hypercholesterolemic patients receiving statin, all available studies were included in this meta-analysis.MethodsA systematic search for eligible studies in the Cochrane library database, Scopus and PubMed was performed. Articles meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…A study on IMPROVE-IT reported a clear benefit in the reduction in major cardiovascular (CV) events with simvastatin and ezetimibe therapy[ 52 ]. The expression of the gene could also influence the lipid-lowering efficacy, and our most recent meta-analysis indicated that the ABCB1 C3435T polymorphism might be a pharmacogenomic biomarker for predicting clinical outcomes in patients with statins[ 53 ]. Therefore, we should consider the effect of statins in the present study, although we discovered that the ABCB1 C3435T polymorphism was related to the all-cause mortality under treatment with clopidogrel in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study on IMPROVE-IT reported a clear benefit in the reduction in major cardiovascular (CV) events with simvastatin and ezetimibe therapy[ 52 ]. The expression of the gene could also influence the lipid-lowering efficacy, and our most recent meta-analysis indicated that the ABCB1 C3435T polymorphism might be a pharmacogenomic biomarker for predicting clinical outcomes in patients with statins[ 53 ]. Therefore, we should consider the effect of statins in the present study, although we discovered that the ABCB1 C3435T polymorphism was related to the all-cause mortality under treatment with clopidogrel in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients carrying the ABCB1 c.3435TT genotype showed a significant decrease in ABCB1 mRNA and protein levels [ 53 , 113 , 114 ]. A meta-analysis on hypercholesterolemic patients receiving statins examined the lipid-lowering efficacy and safety associated with the ABCB1 c.3435C>T. Results indicated that the comparison of CC + CT vs. TT was associated with a significant elevation in the serum HDL-C and total cholesterol levels upon statin treatment, and the ABCB1 c.3435CC vs. TT variants in homozygotes was correlated with decreases in LDL-C. No significant association was instead observed in serum triglycerides levels [ 54 ]. The c.3435C>T polymorphism in ABCB1 can also explain some heterogeneity of adverse response to statins.…”
Section: Pharmacogenetics Of Statinsmentioning
confidence: 99%
“…The c.3435T allele was more frequent in patients with atorvastatin-induced myalgia [ 21 , 55 ]. In addition, an ABCB1 c.3435C>T stratification analysis according to treatment duration found an association with a risk of myopathy in patients treated with statins for more than 5 months [ 54 ]. Currently, literature does report contrasting data on c.3435C>T SNP, whose association with the effect of statins on cholesterol and lipid levels is still debated.…”
Section: Pharmacogenetics Of Statinsmentioning
confidence: 99%
“…95 The organic anion-transporting polypeptide (OATP) 1B1 (gene name SLCOB1) arbitrates the hepatic uptake of all statins to a inconsistent level and the efflux transporters P-Glycoprotein / the breast cancer resistance protein (BCRP, gene name ABCG2) are engaged in the transport of most of the statin from the hepatocytes into bile. 96,97 Therefore drugs like cyclosporine, diltiazem that inhibit P-Glycoprotein may increase statin levels and precipitate toxicity. 98 With narrow therapeutic range drugs such as warfarin and digoxin statin increase anti coagulation effect, the reason expected to be that statin (simvastatin) inhibit metabolism of warfarin through CYP2C9.…”
Section: Drug Interactionsmentioning
confidence: 99%